Residential energy efficiency in Chile: Policies to reduce firewood dependency - Cortes, Alejandra; Rismanchi, Behzad (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
Over 10 million people in Chile are exposed to concentrations of Particulate Matter 2.5 and 10 (PM2.5 – PM10) in excess of the acceptable levels. The main source of emissions in the southern cities is the extensive use of firewood in the residential sector for cooking and heating. Low energy efficiency in buildings and inefficient heating appliances increase firewood combustion intensity and atmospheric pollution. This has led to many cities being declared saturated zones of particulate matter, requiring the implementation of various policies under an Atmospheric Decontamination Plan (ADP). The present research focuses on comparing three housing groups having different implemented strategies and subsidies for improving the energy efficiency of dwellings. A survey was designed to analyze occupants’ fuel consumption patterns and their comfort perception before and after subsidies was applied. Also, it was registered the dwelling intervention to analyze the effectiveness of housing thermal retrofitting. Results showed that thermal retrofitting in housing is random, and does not respond to an accurate study of the interventions’ energy efficiency.